Thailand's trade balance with each of her 15 largest partners: an asymmetry analysis. Issue 3 (13th August 2018) - Bahmani-Oskooee, Mohsen; Kanitpong, Tatchawan
Abstract : Purpose: The purpose of this paper is to assess asymmetric effects of exchange rate changes on Thailand's trade balances. Design/methodology/approach: The design methodology is based on the nonlinear ARDL approach of Shin et al. (2014). Findings: The authors find strong support for the asymmetric effects of exchange rate changes on the Thailand trade balance with most partners, including the three largest partners, China, Japan and the USA. Research limitations/implications: The long-run asymmetric effects revealed that while baht depreciation will hurt Thailand's trade balance with China, it will improve its trade balance with the USA and has no effects with Japan. Practical implications: The trade balance of different partners reacts differently to currency depreciation. Social implications: A currency depreciation that improves the trade balance by promoting exports also helps to reduce the rate of unemployment. Originality/value: No study has assessed the asymmetric effects of exchange rate changes on the Thailand's trade balance with its major partners.